Tecnologias e sociabilidades: processos de organização de catadores de materiais recicláveis - Bortoli, Mari Aparecida (2012)
This research aims to investigate the processes of organization in which the collectors of recyclable materials take part and its relation to production technologies and forms of sociability. The investigation, quantitative and qualitative nature, has as its starting point the experiences of organization of collectors of recyclable materials from Gravataí, county in metropolitan area of Porto Alegre. Techniques of bibliographical, documental and empirical research are used, integrating statistical data, collected through forms, with reports collected in interviews and observations. The survey sample consists of 150 collectors who work in collection activities, organized in groups or alone. It is problematized the way these workers are related to the knowledge built, they way they use it in the work of collecting recyclable materials and also the social forms engendered by them from their relationships in society. The questions guiding the thesis refer to historical events about the organization of collectors of recyclable materials and the mechanisms developed for the social and economic inclusion of this segment of workers. The study shows that experiences around the socioeconomic organization of collectors of recyclable materials involve complex and contradictory relationships. It is poor people who organize themselves into associations or cooperatives so they can act in the collection of recyclable materials. Its inclusion in these organizational forms is related to a set of socio-institutional mechanisms that allow partnerships, agreements and contracts for the provision of services in the area of selective urban collection. The field of new forms of occupation require the use of technologies produced by the pickers themselves and the use of technologies that focus on such workers. It is marked out, in those cases, the inclusion of new products and new ways of doing the collection, including its tools and methodologies, whether for work or screening units or in hangars, or for that which is carried out on the streets.